Dual-analyte electrochemical sensor for fructose and alizarin red S specifically sensitive detection based on indicator displacement assay. (1st October 2019) - Liu, Fen; Kan, Xianwen
Abstract: In this work, a novel dual-analyte electrochemical sensor was developed based on the combination of boronate affinity and indicator displacement assay (IDA) strategy. Reduced graphene oxidation (RGO) and poly(3-aminophenylboronic acid) (pAPBA) were modified on glassy carbon electrode (GCE), which further bound dopamine (DA) via a reversible covalent interaction between the APBA and DA. Due to the higher affinity of pAPBA to the analytes, the bound DA can be displaced by fructose (Fru) or Alizarin Red S (ARS). As an indicator, the decrease of DA current caused by the displacement was used to monitor the concentration of the analyte. For non electro-active molecule, the decrease of DA current was directly proportional to the logarithm of Fru concentration in a range from 7.0 × 10 −8 to 1.0 × 10 −4 mol/L. For electro-active molecule, the current of DA decreased along with the increase of ARS current owing to the displacement, which were combined as a dual-signl for ARS sensitive detection with a linear range of 9.0 × 10 −8 - 1.0 × 10 −5 mol/L. The results of determining analytes with their interferences demonstrated the good specific affinity of the sensor toward the analytes. The dual-analyte electrochemical sensor based on IDA strategy probably provides a potential guidance for multi-analyte facile, sensitive, and specific detection.